First report of a carbapenemase gene blaOXA-181 harbored in a conjugative plasmid in Kluyvera sichuanensis isolated from spinach - Xu Yang; Jinkyung Kim; Nhu-Y Do; Xinhui Li; En Huang; Se-Ran Jun; Sun Hee Moon; Erin L. DiCaprio; Shuting Chen (International Journal of Food Microbiology, 2026)

Calcium input can lower inorganic nitrogen supply through altering soil gross nitrogen transformation processes in karst area - Shuting Yang; Yang Ma; Lijuan Huang; Zepeng Dong; Hui Yang; Kang Ni; Yuelong Wei; Tongbin Zhu; Christoph Müller (Soil and Tillage Research, 2026)

Last deglaciation to early Holocene vegetation and hydrology variations in the Middle Tianshan Mountains: a multi-proxy analysis of a lacustrine-peat sediment core from Chaiwopu Basin - Yunpeng Yang; Yangyang Zhang; Shuting Pu; Xiaona Zhang; Panjie Gong (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Comprehensive analyses of carbapenem-resistant and ESBL-producing bacteria in fresh vegetables and their resistome in the United States - Sun Hee Moon; Xu Yang; Jinkyung Kim; Elizabeth Leighton; Se-Ran Jun; Erin DiCaprio; Chelsea Gale; Shuting Chen; Xinhui Li; En Huang (Food Research International, 2026)

Diverse crop rotation promoted crop yield via microbial networks in North China Plain - Shuting Yu; Yubin Zhao; Tianshu Wang; Shuihong Yao; Yang Gao; Jun Li; Xinhua Peng; Bin Zhang (European Journal of Agronomy, 2026)

pH/temperature dual-responsive antifungal delivery system based on polydopamine-modified montmorillonite for sustained essential oil release - Guixiang Teng; Hongyu Wang; Shuting Zhang; Mengyuan Yu; Yanzan Meng; Meng Zhao; Yan Yang; Peng Pu; Chun Zhang (Applied Clay Science, 2026)

Corrigendum to “Study on maintenance energy and protein requirements of adult yaks in the Qinghai–Tibetan Plateau” [Anim. Feed Sci. Technol. 343 (2026), 116893] - Shengchun Xu; Zhilong Wang; Jiyuan Zhang; Shuting Bao; Shuxiang Wang; Shatuo Chai; Xun Wang; Yingkui Yang; Jiaying Lv; Yijuan Ma (Animal Feed Science and Technology, 2026)

Study on maintenance energy and protein requirements of adult yaks in the Qinghai–Tibetan Plateau - Shengchun Xu; Zhilong Wang; Jiyuan Zhang; Shuting Bao; Shuxiang Wang; Shatuo Chai; Xun Wang; Yingkui Yang; Jiaying Lv; Yijuan Ma (Animal Feed Science and Technology, 2026)

Activating Na4 site via crystalline-phase-engineering enables charge redistribution and stress mitigation in Na4Fe3(PO4)2P2O7 cathodes - Linlin Zhou; Danjing Yang; Shuting Wen; Ling Chen; Chenwei Li; Haifeng Yu; Hao Jiang; Chunzhong Li (Science Bulletin, 2026)

Doped NiFe2O4 spinel oxygen carriers for enhanced H2 production in photo-assisted chemical looping reforming with water splitting under mild conditions - Yunkun Zhao; Shuting Min; Yibo Guo; Guangxuan Chen; Rongjing Wang; Xiaolong Xu; Jing Huang; Yang Hu; Tingting Xu; Xun Wang (Journal of Cleaner Production, 2026)

Legume identity shapes soil multifunctionality and microbial networks in long-term cereal-based rotations - Shuting Yu; Shuo Li; Jin Yang; Kees Jan van Groenigen; Guiying Jiang; Mengru Wang; Beibei Wang; Fang Liu; Haitao Liu; Xiaolei Jie; Shiliang Liu (Applied Soil Ecology, 2026)

Insights into exogenous sources and localized secondary release of polychlorinated biphenyls in Ny-Ålesund - Qingyu Guo; Shuting Liu; Guorui Liu; Wenbin Liu; Lili Yang; Minghui Zheng (Environmental Chemistry Letters, 2026)

Serine metabolism hijacks radiotherapy-driven antitumor immunity via suppressing STING-dependent DNA sensing - Xiaochuan Hong; Yuanqin Yang; Lingling Wu; Shuting Xu; Chao Yang; Tong Cui; Qishan Wang; Zhihao Wu; Xueni Yu; Qi Chen; Hanyu Hong; Qianjiang Chen; et al. (Science Bulletin, 2026)

Correction: Eradication Efficacy of Antimicrobial Peptide CRAMP-34 Against Mixed-Species Biofilms Formed by Staphylococcus aureus and Pseudomonas aeruginosa - Huiming Hu; Miao You; Tengyue He; Lihong Yuan; Fan Wang; Yanshuang Huang; Huizhen Zhu; Ruiqi Chen; Shuting Liu; Wei Wei; Hongzao Yang; Hongwei Chen (International Journal of Peptide Research and Therapeutics, 2026)

rDNA-mediated multicopy integration and gene dosage quantification system for microbial zeaxanthin biosynthesis - Ruijing Ling; Shuting Hou; Xiangzhao Mao; Francesco Secundo; Wei Zhou; Meiyi Xi; Yang Xiao; Bei Gao (World Journal of Microbiology and Biotechnology, 2026)

Rethinking Ship Emission Hotspots: A 100 m Resolution AIS-Based Inventory for Coastal Chinese Waters - Shuting Sun; Huihui Zhao; Xianchao Yang; Li Zhu; Wei Han (Journal of Marine Science and Engineering, 2026)
Existing ship emission inventories for coastal seas are typically gridded at 500 m to 1 km, a resolution too coarse to distinguish navigation channels from anchorage zones. Whether the hotspot patterns reported at such scales reflect true emission geography or are artifacts of spatial averaging remains an open question. We construct a 100 m resolution AIS-based emission inventory for two contrasting coastal environments in eastern China—the Yangtze River estuary and the Wenzhou coastal area—using the STEAM framework, and we quantify spatial concentration with Lorenz curve analyses. At this finer resolution, three emission archetypes become separable: discrete anchorage clusters, bankside berthing bands flanking navigation lanes, and sinuous riverbank traces in confined waterways. Emissions are extremely concentrated: the top 1% of grid cells capture over three-quarters of the total theoretical emission potential (Gini = 0.940), and this pattern persists across all months of 2023. Reaggregating the same data to 1 km reduces the top-1% share by roughly 10%, confirming that coarse gridding systematically understates anchorage contributions while overstating those of transit corridors. A dedicated sensitivity analysis on auxiliary engine load assumptions (±30% perturbation of canonical Jalkanen-style load brackets) shows that, while absolute emission totals carry approximately ±15% uncertainty, the spatial concentration of emissions is highly robust: Across all perturbation scenarios, the Gini coefficient varies by less than 0.01, the top-5% emission share varies by less than 2 percentage points, and the location of top-5% hotspot cells overlaps by ≥97.9% (Jaccard index). The results highlight stationary vessel hotspots—discrete anchorages and bankside berths—as a major and previously underemphasized contributor to the cumulative coastal ship emission budget, complementing rather than replacing the conventional navigation-lane focus, with direct implications for shore power siting, anchorage management, and emission control zone design.

A machine learning-based model for soil iron oxides estimation using fused hyperspectral and multispectral data - Yongshi Tan; Zhenxi Wei; Yan Xiao; Yulin Huang; Zongxin Li; Shuting Yang; Lin Zou; Lanhui Yang; Yusong Deng (Journal of Soils and Sediments, 2026)

Eradication Efficacy of Antimicrobial Peptide CRAMP-34 Against Mixed-Species Biofilms Formed by Staphylococcus aureus and Pseudomonas aeruginosa - Huiming Hu; Miao You; Tengyue He; Lihong Yuan; Fan Wang; Yanshuang Huang; Huizhen Zhu; Ruiqi Chen; Shuting Liu; Wei Wei; Hongzao Yang; Hongwei Chen (International Journal of Peptide Research and Therapeutics, 2026)

LABLF: a multispectral and SAR image fusion method based on least squares-optimized adaptive box-guided and Laplacian-Gaussian filtering - Shuting Yang; Xunqiang Gong; Xiufang Zhou; Yichuang Luo; Yuting Wan; Ailong Ma; Yanfei Zhong (International Journal of Remote Sensing, 2026)

Multi-AGV collision-free scheduling framework with task allocation in high-density warehouses - Zhicheng Yang; Benlian Xu; Shuting Le; Xu Zhou; Mingli Lu; Jinliang Cong; Jian Shi; Zhicheng Jin (Swarm and Evolutionary Computation, 2026)

LDH-based avermectin nanopesticide modulates bioaccumulation, antioxidant responses, and microbiota stability in earthworms' gut - Shuting Yang; Yiqiong Li; Chao Zong; Xinglu Pan; Haonan Wang; Qingkui Fang; Linlin Shi; Fengshou Dong; Haiqun Cao (Pesticide Biochemistry and Physiology, 2026)

Insights into the mechanism of nutty aroma formation by Staphylococcus saprophyticus in fermented sausages - Jikun He; Youqin Duan; Shuting Yang; Fidel Toldrá; Jiong Zheng; Muying Du; Linlin Wang; Nodali Ndraha; Shuyao Wang; Juan Chen (International Journal of Food Microbiology, 2026)

Understanding of a sudden shift from foehn to late spring cold span on the north slope of the Middle Tianshan Mountains with meteorological observation and terrain sensitivity simulation experiments - Maoling Ayitikan; Alaiyi Aiding; Yusufu Musha; Qing He; Chengguang Yang; Wulifan Hanan; Shuting Li; Yuting Zhong; Kai Cheng (Journal of Mountain Science, 2026)

Interactive effects of microplastics, heavy metals, and soil microecology under different irrigation water sources - Rui Yang; Lijuan Huo; Hao Yang; Yan Gong; Gaiqiang Yang; Shuting Tian; Shuhui Cao; Xia Li; Qingwei Ding; Yaqiong Fan; Qi Liu (Applied Soil Ecology, 2026)

Leveraging soil quality assessment for Cd-contaminated farmland through a diagnostic quantitative analysis of multi-dimensional indicators - Yu Gao; Shuting Xiang; Xiulan Yan; Rugang Wang; Xiao Yang (Journal of Hazardous Materials, 2026)

Integrative engineering of biomass-derived CQDs for enhancing photosynthesis of microalgae coupled with bioethanol production - Xiaofeng Liu; Youlian Xu; Yuantao Shen; Jingwen Zhang; Weiyan Zhang; Shuting Ke; Yadong Zhao; Boyang He; Meihua Fan; Zengliang Miao; Xiaolin Zhang; Zhi Liao; et al. (Bioresource Technology, 2026)

Stability and Transport of Ferrihydrite Nanoparticles in Alkaline Soils - Yan Gong; Meiling Wang; Shuting Tian; Qingwei Ding; Xia Li; Gaiqiang Yang; Qi Liu; Juanfang Yang; Lijuan Huo (Water, Air, & Soil Pollution, 2026)

Essential oil-loaded amine-modified HNTs composites for sustained release and enhanced antibacterial performance in root rot control - Guixiang Teng; Hui Yao; Hongyu Wang; Shuting Zhang; Yanzan Meng; Meng Zhao; Yan Yang; Chun Zhang (Applied Clay Science, 2026)

Paleoglacial coverage and paleoclimatic reconstruction of MIS 3b and the gLGM in the Turgen–Asgat Catchment, Altai Mountains - Chang Liu; Liang Liu; Yijie Zhai; Shuting Han; Zheng Yang; Wei Zhang (Journal of Earth System Science, 2026)

Effects of C/N on PHB production, resource recovery, and microbial communities in high-salinity wastewater via SBR - Min Ren; Huining Zhang; Xingnan Guo; Dongxia Zhang; Shuting Zhang; Bixiao Ji; Xiaodong Yang (Environmental Monitoring and Assessment, 2026)

Plastic-derived dissolved organic matter amplifies the bioavailability and toxicity of short-chain chlorinated paraffins in Chlorella vulgaris - Changqing Yao; Shuting Fang; Yiquan Huang; Baohua Huang; Chao Chen; Qijun Ruan; Weixin Liang; Shenghong Yang; Shuqin Liu (Journal of Hazardous Materials, 2026)

Free radical mechanisms of halogen coexistence promoting pollutants formation - Mingxuan Wang; Shuting Liu; Linjun Qin; Qingyu Guo; Guorui Liu; Dong Cao; Lili Yang; Minghui Zheng (Journal of Environmental Sciences, 2026)

Mechanistic insights into organic acid-enhanced polycyclic aromatic hydrocarbon release from soil: Disruption of metal cation bridges and charge-assisted hydrogen bonds - Shuting Wei; Yue Yuan; Weifeng Chen; Jinzhi Ni; Huiying Zhang; Meiyu Yang; Ran Wei (Environmental Research, 2026)

Characteristics and controlling factors of soil micro-climate in a subtropical re-vegetation catchment: Insights from continuous moisture and temperature observations - Jiapan Xu; Muxing Liu; Siqi Mei; Qian Yang; Jun Zhang; Jun Yi; Shuting Ding; Yan Tan (Plant and Soil, 2026)

Multi-objective optimization study of wire mesh mist eliminator based on RSM and NSGA-II - Shuting Zhong; Shaochen Yang; Rulei Sun; Ruifeng Tian; Sichao Tan; Chaojun Deng; Bo Wang (Annals of Nuclear Energy, 2026)

Cadmium immobilization and selenium mobilization by Citrobacter freundii in soil-rice system: a trade-off between remediation efficacy and soil microbial community integrity - Fuyu GUO; Tianao YU; Rui ZHANG; Tingting CHU; Meng ZHU; Shuting ZAN; Fengxiang X. HAN; Ruyi YANG (Pedosphere, 2026)

Laboratory-scale characteristics of micro-slip during fault quiescence and implications for injection-induced reactivation stability - Ning Yang; Peng-Zhi Pan; Shuting Miao; Wenbo Hou (International Journal of Rock Mechanics and Mining Sciences, 2026)

An extra-large panicle gene ELP1 from wild rice Oryza officinalis increases grain number and grain yield - Jiachen Ma; Mei Li; Yanan Lin; Jinjin Lian; Yizhengnan Zhu; Jing Yang; Wenfan Hu; Luyi Zhang; Shuting Li; Weilin Zhang (Theoretical and Applied Genetics, 2026)

Theoretical, experimental and numerical study on mechanical properties of innovative PSRC floor - Wenkang Wang; Shuting Liang; Xiaojun Zhu; Jian Yang; Tiancheng Han; Yiwei Xu; Yinjie Lu (Engineering Structures, 2025)

Performance analysis of seismically-damaged precast shear wall with a multi-stage energy dissipation mechanism after repair - Jian Yang; Shuting Liang; Jingbo Su; Xiaojun Zhu; Longji Dang; Yinjie Lu (Engineering Structures, 2025)

Synergistic microenvironmental modulation of atomically dispersed metal centers applied for zinc‑carbon dioxide batteries - Zhangxin Xu; Mingyang Liu; Yanqi Yang; Shuting Zhang; Jingjing Guan; Liping Zhang; Jinlong Zou; Baojiang Jiang (Chemical Engineering Journal, 2025)

High pressure torsion technology applied to ZnO nanomaterials for enhancing the room-temperature HCl sensing performance - Shuting Wei; Dan Yang; Renquan Guan; Peng Xu; Yuxin Wang; Yingmin Teng; Aicen Li; Junkai Zhang; Huaqiao Tan; Lili Wang; Zheng Lou; Wenjuan Zhang; et al. (Chemical Engineering Journal, 2025)

A comprehensive analysis of stroke risk factors and development of a predictive model using machine learning approaches - Songquan Xie; Shuting Peng; Long Zhao; Binbin Yang; Yukun Qu; Xiaoping Tang (Molecular Genetics and Genomics, 2025)

FAK mediates mechanical signaling to maintain epithelial homeostasis through YAP/TAZ-TEADs - Yang Peng; Qiuyun Yuan; Shuting Zhou; Jianguo Gan; Zhengzhong Shen; Xiaoqiang Xia; Yuchen Jiang; Qianming Chen; Yao Yuan; Gu He; Qiang Wei; Xiaodong Feng (Histochemistry and Cell Biology, 2025)

Daily Runoff Prediction in Xijiang River Basin Based on FOA ‐ TCN ‐ BiLSTM Model - Lei Guo; Chaoqiang Yang; Qingqing Tian; Shuting Zhang; Qiongyao Wang (International Journal of Climatology, 2025)
Accurate and reliable daily runoff forecasting plays a vital role in water resource management, flood warning and operational scheduling. However, runoff prediction is challenging due to its nonlinear and non‐stationary nature, influenced by climate change, topography and human activities. To improve forecasting accuracy, this study proposes a hybrid TCN‐BiLSTM model optimised by the Fruit Fly Optimization Algorithm (FOA) for daily runoff prediction in the Xijiang River basin. The model first utilises the Temporal Convolutional Network (TCN) to extract temporal features, then employs the Bidirectional Long Short‐Term Memory (BiLSTM) network to capture temporal dependencies, and finally optimises key hyperparameters of the model using the FOA to enhance overall performance. Taking the four hydrological stations in the Xijiang River basin, including WX, WZ, DHJK and GG, as examples, the model exhibits outstanding performance in both single‐step and multi‐step prediction tasks. Taking the WX station as a representative example, the model achieved an MSE, MAE, and R 2 of 0.888 × 10 6 m 3 /s, 0.530 × 10 3 m 3 /s and 0.960 on the test set, respectively. Compared with the BiLSTM model, the MSE and MAE decreased by 63.27% and 40.69%, while the R 2 increased by 7.49%. Compared with the TCN model, the MSE and MAE decreased by 59.60% and 39.71%, with an R 2 improvement of 6.31%. Relative to the TCN‐BiLSTM model, the MSE and MAE were reduced by 43.15% and 26.38%, and the R 2 increased by 3.11%. Moreover, the R 2 values for the test sets at all four stations reached 0.955 or higher, further confirming the model's stability and generalisation capability across multiple regions. The results indicate that the FOA‐TCN‐BiLSTM model demonstrates significant advantages in enhancing runoff prediction accuracy and generalisation, making it particularly suitable for practical engineering applications such as flood forecasting, water resource management, and regional hydrological risk assessment, thus holding promising application prospects.

The influence of emotion on human thermal comfort: based on netted meta-analysis - Kun Zhou; Hao Yang; ShuTing Li; YaYu Feng; TianYi Pang; YanKai Zhao; Yi Xu (Energy and Buildings, 2025)

Biomimetic hydrogel microsphere encapsulated superoxide dismutase enzymes alleviate postoperative peritoneal adhesion by modulating oxidative stress-inflammation cycles via Piezo1 mechanosensitive channels - Shuting Yang; Chao Qu; Xuetao Yuan; Ke Liu; Kai Deng; Jiayin Du; Yuanbo Wang; Man Xu; Li Zhang; Mingzhen Zhang; Ting Liang; Xuqi Li (Chemical Engineering Journal, 2025)

Shaking table test of a frame structure with phononic-like crystal polymer concrete seismic mitigation raft foundation - Shuting Liang; Yuanyuan Sun; Xiaojun Zhu; Linchang Miao; Zhongzhen Xie; Jian Yang (Soil Dynamics and Earthquake Engineering, 2025)

Study on complex failure modes of super-long piles in deep-water and soft-clay seabed under multiple combined loads - Linlin He; Xuan Liu; Yuanshi Xie; Shuting Cao; Yue Liang; Yang Liu (Ocean Engineering, 2025)

All-screen-printed tactile sensor for robotic arm via polymeric thermal foaming - Xun Fu; Yugang Chen; Shuting Xie; Mengyu Cao; Qiang Zhao; Yixiao Liu; Yang Li; Shasha Wang; Xiaogang Cheng; Linghai Xie (Chemical Engineering Journal, 2025)

Validity of Smartwatches for Estimating Energy Expenditure During Aerobic Dance - Xueyuan Zhao; Xingyi Ding; Junchao Yang; Shuting Yan; Hong Wang; Kuan Tao; Junqiang Qiu (Journal of Science in Sport and Exercise, 2025)

Experimental study on the flexural behavior of large-span prestressed and steel-reinforced concrete slabs - Tiancheng Han; Shuting Liang; Xiaojun Zhu; Wenkang Wang; Jian Yang (Engineering Structures, 2025)

Impact of watershed-scale land restoration on soil microbial communities and their functions: Insights from metagenomic analysis - Rui Yang; Shaoqing Guo; Lijuan Huo; Gaiqiang Yang; Shuting Tian (Environmental Research, 2025)

Targeting 5-HT to Alleviate Dose-Limiting Neurotoxicity in Nab-Paclitaxel-Based Chemotherapy - Shuangyue Pan; Yu Cai; Ronghui Liu; Shuting Jiang; Hongyang Zhao; Jiahong Jiang; Zhen Lin; Qian Liu; Hongrui Lu; Shuhui Liang; Weijiao Fan; Xiaochen Chen; et al. (Neuroscience Bulletin, 2025)

Spectral and Topological Abnormalities of Resting and Task State EEG in Chinese Children with Developmental Dyslexia - Yaqi Yang; Shuting Huo; Jie Wang; Urs Maurer (Brain Topography, 2025)
Developmental dyslexia (DD) is a common reading disorder with neurological underpinnings; however, it remains unclear whether Chinese children with DD exhibit spectral power or network topology abnormalities. This study investigated spectral power and brain network topology abnormalities using electroencephalography (EEG) during resting states and a one-back Chinese-Korean character task in 85 Hong Kong Chinese children with DD and 51 typically developing peers (ages 7–11). EEG signals were transformed using the Fast Fourier Transform to estimate spectral power. Functional connectivity matrices were derived using the phase-lag index, and network topology was assessed via minimum spanning tree (MST) analysis. The results suggested that children with DD showed reduced alpha power over central, frontal, temporal, parietal, and occipital scalp areas at rest, and over central and frontal areas during the task. MST results revealed decreased beta band integration at rest but increased alpha band integration during the one-back task. Familiar Chinese stimuli elicited greater alpha and beta power and lower beta band integration compared to unfamiliar Korean stimuli. Moreover, resting-state beta band integration correlated positively with reading fluency in children with DD. These findings point to inhibitory control deficits and cortical hyperactivation in Chinese DD, reflected in disrupted large-scale network topology, and highlight the alpha band as a potential biomarker. They also demonstrate that language familiarity modulates neural efficiency and recruits compensatory networks. Overall, the study provides new insights into the neural basis of reading difficulties in Chinese children with DD.

Radical inhibition mechanisms of ammonium sulfate on industrial organic pollutants in copper-catalyzed reactions - Shuting Liu; Guorui Liu; Mingxuan Wang; Linjun Qin; Qingyu Guo; Da Li; Lili Yang; Minghui Zheng (Journal of Environmental Chemical Engineering, 2025)

Benzalkonium chloride disinfection increases the difficulty of controlling foodborne pathogens identified in aquatic product processing - Yaming Ge; Yu Xue; Qiao Yang; Wanchuan Xing; Shuting Zhu; Wei Jiang; Junzhi Liu (Journal of Hazardous Materials, 2025)

A low-energy-consumption method simultaneously achieving rocksalt domains coating and Al-doping for Li-rich layered cathode material - Xiaoyuan Zhang; Yange Yang; Xiangnan Li; Huishuang Zhang; Hongyun Yue; Hongyu Dong; Yongfang Li; Shuting Yang; Yanhong Yin (Chemical Engineering Journal, 2025)

Quantifying permafrost thawing and its impact on lake storage dynamics in the Qinghai-Tibet Plateau - Shuting Ji; Pan Wu; Lin Chen; Yingjie Yang; Xuehui Pi; Jeffrey M. McKenzie; Xiuyu Liang (Journal of Hydrology, 2025)

Solid membrane-based aqueous lithium extraction and adsorption: Advances, challenges, and prospects - Yueru Yang; Shumin Bi; Faquan Wang; Xinyu Pan; Tianci Yang; Shui Hu; Shuting Tang; Qingxiu Jia (Chemical Engineering Journal, 2025)

Knockdown of the Clock gene in the liver aggravates MASLD in mice via inhibiting lipophagy - Shuhong Yang; Xinxin Ren; Jia Liu; Yan Lei; Minqian Li; Fang Wang; Shuting Cheng; Junjie Ying; Jie Ding; Xiaohui Chen (Molecular and Cellular Biochemistry, 2025)

A novel directed enzymolysis strategy for the preparation of umami peptides in Stropharia rugosoannulata and its mechanism of taste perception - Daoyou Chen; Mingli Rong; Shuting Tang; Chuanxi Zhang; Hao Wei; Zhaoting Yuan; Tingwei Miao; Hucheng Song; Haiming Jiang; Yan Yang; Lujia Zhang (Food Chemistry, 2025)

QSAR modeling on aromatase inhibitory activity of 23 triazole fungicides by tritium-water release assay - Kun Qiao; Shuting Wang; Aoxue Wang; Zhuoying Liang; Siyu Yang; Yongfang Ma; Shuying Li; Qingfu Ye; Wenjun Gui (Environmental Pollution, 2025)

Regulating surface band structure of anisotropic SrTiO3 via ultrathin TiO2 layer to promote spatial charge separation - Shuting Zhang; Honghuo Wang; Tingting Wu; Wenjiao Chang; Yifan Li; Junying Wang; Yongqiang Yang; Lei Wang (Chemical Engineering Journal, 2025)

The impact of aflatoxin B1 on animal health: Metabolic processes, detection methods, and preventive measures - Tianyang Wang; Runzi Cui; Hai-Fan Yu; Dian Yang; Shuting Zhang; Yuzhe Nie; Chun-Bo Teng (Toxicon, 2025)

Self-cleaning micro/nano graded porous groove structure fiber membranes by coaxial spinning for purification of dye wastewater - Wanwan Peng; Shuting Tian; Shuangshuang Li; Jingcheng Wu; Daqing Wu; Peng Zhou; Hongjie Li; Yi He; Yang Bai (Environmental Research, 2025)

Effect of CNF ratio and pressure on structural and electrochemical performance of hybrid hydrogel for flexible free-standing electrode and sensors - Xiping Ding; Jiajia Shan; Shuting Yang; Junyan Liu; Chen Jiang; Shitao Yu; Qiong Wu (Carbohydrate Polymers, 2025)

Mitigating impacts of hot weather on outdoor workers by attaching phase change materials based on body mapping of physiology - Shuting Gu; Zhen Yang; Hongyu Chen; Wenwei Ma; Hongyi Gao; Ying Zhang; Jingxian Xu (Building and Environment, 2025)

Multi-objective optimization design of double-hooked corrugated plate dryer based on NSGA-II - Zhong Shuting; Sun Rulei; Li Yang; Qin Qi; Deng Chaojun; Wang Bo; Tian Ruifeng (Annals of Nuclear Energy, 2025)

Elucidating the role of double-confined effect in hollow MOFs/GO catalytic membrane for deep arsenic pollution treatment - Jiangdong Dai; Lili Li; Xiaohua Tian; Ruilong Zhang; Dayi Yang; Qiaoyu Gao; Shuting Liu; Jun Zhao; Jian Ye; Xiaobo Zhang; Yi Wang (Desalination, 2024)

Litter richness, functional identity, and chemical properties affect soil properties in boreal forest soil in Northeast China: a laboratory study - Shengfang Wang; Qianru Ji; Shuting Zhao; Siru Guo; Xiaochao Ji; Xiting Zhang; Yanbo Yang; Huimei Wang; Wenjie Wang (Plant and Soil, 2024)

Free radical mechanisms of ammonium sulfate as intensively used industrial materials on suppressing organic pollutants - Shuting Liu; Guorui Liu; Mingxuan Wang; Linjun Qin; Qingyu Guo; Da Li; Lili Yang; Minghui Zheng (Science of The Total Environment, 2024)

Formation of persistent free radicals from epigallocatechin Gallate in tea processing and their implications on DNA damage and cell cytotoxicity - Linjun Qin; Lili Yang; Manabu Shiraiwa; Francesco Faiola; Yujue Yang; Shuting Liu; Guorui Liu; Minghui Zheng; Guibin Jiang (Food Chemistry, 2024)

Theoretical investigation of two ideal radiative cooling materials and radiative sky water-cooling module with ideal selective radiative materials - Xiufeng Yang; Shuting Wang; Dong Zhang; Jia Yu (Energy and Buildings, 2024)

Natural enzyme cascade bimetallic sulfide MoCuSx nanozyme for synergistic photothermal/photodynamic enhanced chemodynamic antimicrobial therapy of wound infection - Caiyun Xu; Junqin Li; Chunlei Ou; Jing Yang; Shuting Fu; Weiqing Hu; Li Wang; Zefeng Wang; Luo Hai; Le Deng; Dinggeng He (Chemical Engineering Journal, 2024)

Controllable preparation of graphene glass fiber fabric towards mass production and its application in self-adaptive thermal management - Ruojuan Liu; Fan Yang; Shuting Cheng; Xianghe Yue; Fushun Liang; Wenjuan Li; Jingnan Wang; Qinchi Zhang; Liangyu Zou; Hao Yuan; Yuyao Yang; Kangyi Zheng; et al. (Science Bulletin, 2024)

Parameter analysis and dual-objective optimization of the hydraulic power take-off system of a floating wind-wave hybrid system - Shuting Huang; Jun Wang; Mingyu Yang; Ge Dong; Yuanzhi Wang; Yanjun Liu (Ocean Engineering, 2024)

Earthworm gut bacteria facilitate cadmium immobilization through the formation of CdS nanoparticles - Bo Xu; Tingting Chu; Ranran Zhang; Ruyi Yang; Meng Zhu; Fuyu Guo; Shuting Zan (Chemosphere, 2024)

Suppressing the Jahn–Teller effect in Mn-based Prussian blue analogues by linear (N O) anions - Qinghao Han; Zonghua Yang; Ya’nan Hu; Shuting Gao; Xingjun Liu; Cuiping Wang; Jiajia Han (Chemical Engineering Journal, 2024)

Recent Ventures in Interdisciplinary Arctic Research: The ARCPATH Project - Astrid E. J. Ogilvie; Leslie A. King; Noel Keenlyside; François Counillon; Brynhildur Daviđsdóttir; Níels Einarsson; Sergey Gulev; Ke Fan; Torben Koenigk; James R. McGoodwin; Marianne H. Rasmusson; Shuting Yang (Advances in Atmospheric Sciences, 2024)

A cell-free fluorescence biosensor based on allosteric transcription factor NalC for detection of pentachlorophenol - Shuting Chen; Chen Zhao; Xiaodan Kang; Xi Zhang; Bin Xue; Chenyu Li; Shang Wang; Xiaobo Yang; Chao Li; Zhigang Qiu; Jingfeng Wang; Zhiqiang Shen (Biotechnology Letters, 2024)

Spatial-Temporal Ship Pollution Distribution Exploitation and Harbor Environmental Impact Analysis via Large-Scale AIS Data - Xinqiang Chen; Shuting Dou; Tianqi Song; Huafeng Wu; Yang Sun; Jiangfeng Xian (Journal of Marine Science and Engineering, 2024)
Ship pollution emissions have attracted increasing attention in the maritime field due to the massive growth of maritime traffic activities. It is important to identify the ship emissions (SEs) magnitude and corresponding spatial and temporal distributions for the purposes of developing appropriate strategies to mitigate environment pollution. The aim of this study was to estimate ship pollution emissions with various typical merchant ship types under different sailing conditions. We estimated the emission variation with a ship traffic emission assessment model (STEAM2), and then the ship pollution emission distribution was further visualized using ArcGIS. We collected data from the automatic identification system (AIS) for ships in New York Harbor and further analyzed the spatiotemporal distribution of pollutant emissions from ships. The experimental results demonstrate that the ship pollutant emission volume in the New York Harbor area in 2022 was 3340 t, while the pollution in terms of CO, SO2, CXHX, PM10, NOX, and PM2.5 was 136, 1421, 66, 185, 1384, and 148 t, respectively. The overall SEs from container ships, passenger ships, and tankers account for a large amount of pollution discharge. The pollutant emissions of container ships are significantly greater than that of their counterparts. Moreover, the spatiotemporal distributions of ship pollutant discharge can vary significantly among different ship types and sailing conditions.

Dynamic coupling between cementation and porosity evolution of the Chang 8 tight sandstone reservoir, Ordos Basin: Insights from in-situ microanalysis - Ruiliang Guo; Weiwei Yang; Xiuqin Deng; Shuting Shi; Shutong Li; Junli Qiu; Jiaqiang Zhang; Junlin Chen; Lewei Hao; Xiaofeng Ma; Dongxu Ma; Peng Liu (Marine and Petroleum Geology, 2024)

Green fabrication of nanocomposite films using lignin nanoparticles and PVA: Characterization and application - Qingsong Zheng; Pamela Owusu Osei; Shaoran Shi; Shuting Yang; Xiaomeng Wu (Food Bioscience, 2024)

Efficacy and safety of proton pump inhibitors on cardiovascular events and inflammatory factors in patients with upper gastrointestinal bleeding undergoing dual antiplatelet therapy - Shuting Yang; Linni Shi (Inflammopharmacology, 2024)

Correction to: Near‑global summer circulation response to the spring surface temperature anomaly in Tibetan Plateau –– the GEWEX/LS4P first phase experiment - Yang Zhang; Yan Pan; Yongkang Xue; Ismaila Diallo; Xubin Zeng; Shuting Li; J. David Neelin; William K. M. Lau; Aaron A. Boone; Frederic Vitart; Tandong Yao; Qi Tang; et al. (Climate Dynamics, 2024)

Ocean response to a century of observation-based freshwater forcing around Greenland in EC-Earth3 - Marion Devilliers; Shuting Yang; Annika Drews; Torben Schmith; Steffen M. Olsen (Climate Dynamics, 2024)
The acceleration of Greenland ice sheet melting over the past decades is raising concern regarding the impacts on ocean circulation in the North Atlantic and Arctic regions. Global climate models struggle to assess these impacts as they do not include a realistic amount of meltwater from the Greenland ice sheet. Using an extended observation-based dataset of runoff and solid ice discharge for the recent historical period (1920–2019), we force the EC-Earth3 climate model following the ensemble approach and protocol of a previous study using a different model. We observe a slight increase of the ensemble mean AMOC with a large spread in the response: $$0.20± 0.81$$ 0.20 ± 0.81 Sv for the maximum AMOC at 45 $$^{° }$$ ∘ N. We notice that members with a strong initial AMOC state (18 Sv) show a strengthening of the AMOC, while members with intermediate AMOC strength between 16 and 18 Sv are not affected by the freshwater forcing. Weaker initial AMOC members respond with a mean weakening of $${-}\,0.21± 0.58$$ - 0.21 ± 0.58 Sv of the AMOC. The AMOC ensemble spread is reduced by half in the freshwater forced ensemble at the end of the experiment and the negative trend is stronger compared to historical simulations without the forcing. This suggests the possible ability of the freshwater to constrain AMOC variability on multi-decadal time-scales. Comparison of the two ten member ensembles with ORAS5 reanalysis shows a reduction of the surface temperature and salinity biases in the freshwater forced ensemble in key regions such as the North Atlantic subpolar gyre and the Beaufort Gyre relative to the historical simulations. Recent trends are also more aligned with reanalysis in those regions. Arctic Ocean Atlantic Water subsurface core temperature is also closer to reanalysis but still strongly biassed. Members with a high AMOC initial state display an unrealistic Atlantic water layer core depth.

The effects of different drying methods on the flavor profile of wheat germ using E-nose and GC-IMS - Yang Zhong; Gexing Zhang; Fangqin Zhang; Shuting Lin; Mei Wang; Yue Sun; Jin Liang; Xueling Li (Journal of Cereal Science, 2024)

The toxicity of polystyrene micro- and nano-plastics on rare minnow (Gobiocypris rarus) varies with the particle size and concentration - Tingting Chu; Rui Zhang; Fuyu Guo; Meng Zhu; Shuting Zan; Ruyi Yang (Aquatic Toxicology, 2024)

Near-global summer circulation response to the spring surface temperature anomaly in Tibetan Plateau –– the GEWEX/LS4P first phase experiment - Yang Zhang; Yan Pan; Yongkang Xue; Ismaila Diallo; Xubin Zeng; Shuting Li; J. David Neelin; William K. M. Lau; Aaron A. Boone; Frederic Vitart; Tandong Yao; Qi Tang; et al. (Climate Dynamics, 2024)
Subseasonal to seasonal (S2S) prediction of droughts and floods is one of the major challenges of weather and climate prediction. Recent studies suggest that the springtime land surface temperature/subsurface temperature (LST/SUBT) over the Tibetan Plateau (TP) can be a new source of S2S predictability. The project “Impact of Initialized Land Surface Temperature and Snowpack on Subseasonal to Seasonal Prediction (LS4P)” was initiated to study the impact of springtime LST/SUBT anomalies over high mountain areas on summertime precipitation predictions. The present work explores the simulated global scale response of the atmospheric circulation to the springtime TP land surface cooling by 16 current state-of-the-art Earth System Models (ESMs) participating in the LS4P Phase I (LS4P-I) experiment. The LS4P-I results show, for the first time, that springtime TP surface anomalies can modulate a persistent quasi-barotropic Tibetan Plateau-Rocky Mountain Circumglobal (TRC) wave train from the TP via the northeast Asia and Bering Strait to the western part of the North America, along with the springtime westerly jet from TP across the whole North Pacific basin. The TRC wave train modulated by the TP thermal anomaly play a critical role on the early summer surface air temperature and precipitation anomalies in the regions along the wave train, especially over the northwest North America and the southern Great Plains. The participant models that fail in capturing the TRC wave train greatly under-predict climate anomalies in reference to observations and the successful models. These results suggest that the TP LST/SUBT anomaly via the TRC wave train is the first order source of the S2S variability in the regions mentioned. Furthermore, the TP surface temperature anomaly can influence the Southern Hemispheric circulation by generating cross-equator wave trains. However, the simulated propagation pathways from the TP into the Southern Hemisphere show large inter-model differences. More dynamical understanding of the TRC wave train as well as its cross-equator propagation into the Southern Hemisphere will be explored in the newly launched LS4P phase II experiment.

On the Quartic Korteweg–de Vries hierarchy of nonlinear Rossby waves and its dynamics - Shuting Hou; Ruigang Zhang; Zhihui Zhang; Liangui Yang (Wave Motion, 2024)

A remote sensing-based strategy for mapping potentially toxic elements of soils: Temporal-spatial-spectral covariates combined with random forest - Xibo Xu; Zeqiang Wang; Xiaoning Song; Wenjie Zhan; Shuting Yang (Environmental Research, 2024)

Profile and nano-scale distribution of soil organic carbon for upland and paddy soils from an alluvial plain in South China - Shuting Jiang; Xucheng Liu; Yang Lu; Jiahui Wu; Leiyi Zhang; Jinxi Wang; Wencheng Wu (Chemical Geology, 2023)

Mettl13 protects against cardiac contractile dysfunction by negatively regulating C-Cbl-mediated ubiquitination of SERCA2a in ischemic heart failure - Shuting Yu; ZhiYong Sun; Xiuzhu Wang; Tiantian Ju; Changhao Wang; Yingqi Liu; Zhezhe Qu; KuiWu Liu; Zhongting Mei; Na Li; Meixi Lu; Fan Wu; et al. (Science China Life Sciences, 2023)

Key geodynamic processes and driving forces of Tethyan evolution - Zhong-Hai Li; Fengyuan Cui; Shuting Yang; Xinyi Zhong (Science China Earth Sciences, 2023)

Effect of urban pavement on nutrient strategies of common greening tree species in northern China - Jinyan Yang; Lide Fan; Dan Song; Shuting Liu; Haifang Li; Richard Hauer; Yujie Xia; Yuwu Li (Urban Forestry & Urban Greening, 2023)

Measuring and modeling the effects of green barriers on the spatial distribution of fine particulate matter at roadside - Xin Chen; Jie Wu; Wenbin Yang; Zhanyong Wang; Shuting Chen; Xisheng Hu; Kaifa Lu; Zhongmou Fan; Mei Lin; Pu Chen (Urban Climate, 2023)

Soil calcium constrains nitrogen mineralization and nitrification rates in subtropical karst regions - Shuting Yang; Lin Yang; Dongni Wen; Lijun Liu; Kang Ni; Jianhua Cao; Tongbin Zhu; Christoph Müller (Soil Biology and Biochemistry, 2023)

Distribution and biodegradation of nonextractable polycyclic aromatic hydrocarbons in particle-size aggregates of field-contaminated soils - Ran Wei; Shuting Wei; Cheng Yao; Weifeng Chen; Liuming Yang; Jinzhi Ni (Journal of Soils and Sediments, 2023)

Medium-chain triglyceride-stabilized docetaxel-loaded HSA nanoparticles effectively inhibited metastatic non-small cell lung cancer - Yunlong Cheng; Xiaoying Pang; Jing Wu; Lingling Zhou; Jinxu Cao; Liuchang Wang; Kang Qian; Peng Yang; Minjun Xu; Dongyu Sheng; Ran Meng; Pengzhen Wang; et al. (Drug Delivery and Translational Research, 2023)

Constraining CMIP6 estimates of Arctic Ocean temperature and salinity in 2025-2055 - Helene Reinertsen Langehaug; Hanne Sagen; A. Stallemo; Petteri Uotila; L. Rautiainen; Steffen Malskær Olsen; Marion Devilliers; Shuting Yang; E. Storheim (Frontiers in Marine Science, 2023)
Global climate models (CMIP6 models) are the basis for future predictions and projections, but these models typically have large biases in their mean state of the Arctic Ocean. Considering a transect across the Arctic Ocean, with a focus on the depths between 100-700m, we show that the model spread for temperature and salinity anomalies increases significantly during the period 2025-2045. The maximum model spread is reached in the period 2045-2055 with a standard deviation 10 times higher than in 1993-2010. The CMIP6 models agree that there will be warming, but do not agree on the degree of warming. This aspect is important for long-term management of societal and ecological perspectives in the Arctic region. We therefore test a new approach to find models with good performance. We assess how CMIP6 models represent the horizontal patterns of temperature and salinity in the period 1993-2010. Based on this, we find four models with relatively good performance (MPI-ESM1-2-HR, IPSL-CM6A-LR, CESM2-WACCM, MRI-ESM2-0). For a more robust model evaluation, we consider additional metrics (e.g., climate sensitivity, ocean heat transport) and also compare our results with other recent CMIP6 studies in the Arctic Ocean. Based on this, we find that two of the models have an overall better performance (MPI-ESM1-2-HR, IPSL-CM6A-LR). Considering projected changes for temperature for the period 2045-2055 in the high end ssp585 scenario, these two models show a similar warming in the Mid Layer (300-700m; 1.1-1.5 ° C). However, in the low end ssp126 scenario, IPSL-CM6A-LR shows a considerably higher warming than MPI-ESM1-2-HR. In contrast to the projected warming by both models, the projected salinity changes for the period 2045-2055 are very different; MPI-ESM1-2-HR shows a freshening in the Upper Layer (100-300m), whereas IPSL-CM6A-LR shows a salinification in this layer. This is the case for both scenarios. The source of the model spread appears to be in the Eurasian Basin, where warm waters enter the Arctic. Finally, we recommend being cautious when using the CMIP6 ensemble to assess the future Arctic Ocean, because of the large spread both in performance and the extent of future changes.

Cell apoptosis in the testis of male rats is elevated by intervention with β-endorphin and the mu opioid receptor - Xiaofan Xiong; Siyu Zhang; Lulu Zang; Yanlong Xin; Yixin Pang; Shuting Zhang; Yu Yang; Rongfu Tu; Lingyu Zhang; Yuefeng Du; Juan Yang (Reproductive Biology, 2023)

Fabrication and characterizations of Zn-doped SnO2-Ti4O7 anode for electrochemical degradation of hexafluoropropylene oxide dimer acid and its homologues - Zehong Yang; Qiongfang Zhuo; Wenlong Wang; Shuting Guo; Jianfeng Chen; Yanliang Li; Sihao Lv; Gang Yu; Yongfu Qiu (Journal of Hazardous Materials, 2023)

Big-sized trees and higher species diversity improve water holding capacities of forests in northeast China - Yanbo Yang; Lixin Jing; Qi Li; Chentao Liang; Quanxing Dong; Shuting Zhao; Yuwen Chen; Danqi She; Xu Zhang; Lei Wang; Guanchao Cheng; Xiting Zhang; et al. (Science of The Total Environment, 2023)

Weibull distribution models for describing soil hydraulic properties over the entire matric suction range - Zhenlei Yang; Zi Li; Xin Tong; Shengjie Hu; Jun Wang; Shuting Ji; Ling Li (Journal of Hydrology, 2023)

Non-oxide supported Pt-metal-group catalysts for efficiently CO and toluene co-oxidation: Difference in water resistance and degradation intermediates - Fukun Bi; Shuting Ma; Bin Gao; Yang Yang; Lexun Wang; Fuhao Fei; Jingcheng Xu; Yuandong Huang; Minghong Wu; Xiaodong Zhang (Fuel, 2023)

Tree species richness and arbuscular mycorrhizal tree fraction of leaf litter increase carbon and nitrogen retention in soil with macroaggregate and glomalin accrual - Xiaochao Ji; Shengfang Wang; Siru Guo; Shuting Zhao; Quanxing Dong; Cholil Yun; Xiting Zhang; Yanbo Yang; Wenjie Wang; Huimei Wang (Plant and Soil, 2023)

Internal multi-centennial variability of the Atlantic Meridional Overturning Circulation simulated by EC-Earth3 - Virna L. Meccia; Ramón Fuentes-Franco; Paolo Davini; Katinka Bellomo; Federico Fabiano; Shuting Yang; Jost von Hardenberg (Climate Dynamics, 2023)
We report a multi-centennial oscillation of the Atlantic Meridional Overturning Circulation (AMOC) simulated by the EC-Earth3 climate model under the pre-industrial climate. This oscillation has an amplitude of ~ 6 Sv and a period of ~ 150 years and significantly impacts the atmosphere. We find that it is a self-sustained low-frequency internal variability, driven by the accumulation of salinity anomalies in the Arctic and their release into the North Atlantic, affecting the water column stability and the deep convection. Sea ice plays a major role in creating the salinity anomaly in the Arctic, while the anomalous Arctic oceanic circulation, which drives the exchange of liquid freshwater between the Arctic and the open ocean, is the main responsible for its southward propagation. Interestingly, EC-Earth3 simulations with increased greenhouse concentrations, and therefore under a warmer climate, do not exhibit these strong AMOC fluctuations. We hypothesize that in a quasi-equilibrium climate with a global air surface temperature 4.5° higher than the pre-industrial period, the low amount of sea ice in the high latitudes of the North Atlantic is no longer able to trigger the mechanism.

Correction to: Assessing the influence of sea surface temperature and arctic sea ice cover on the uncertainty in the boreal winter future climate projections - Ho-Nam Cheung; Noel Keenlyside; Torben Koenigk; Shuting Yang; Tian Tian; Zhiqing Xu; Yongqi Gao; Fumiaki Ogawa; Nour-Eddine Omrani; Shaobo Qiao; Wen Zhou (Climate Dynamics, 2023)

Fabrication of covalent organic frameworks modified nanofibrous membrane for efficiently enriching and detecting the trace polychlorinated biphenyls in water - Yuancai Lv; Jiachen Ma; Zhendong Yu; Shuting Liu; Guifang Yang; Yifan Liu; Chunxiang Lin; Xiaoxia Ye; Yongqian Shi; Minghua Liu (Water Research, 2023)

An inorganic-organic-polymeric nanovehicle for targeting delivery of doxorubicin: Rational assembly, pH-stimulus release, and dual hyperthermia/chemotherapy of hepatocellular carcinoma - Jianying Yang; Zhao Wang; Chunhong Mo; Haikun Luo; Shuting Li; Qian Mo; You Qin; Fan Yang; Xinchun Li (Journal of Photochemistry and Photobiology B: Biology, 2023)

Rapid degradation of PFOA by the activated peroxymono-sulfate with FeCo/MoS2 catalyst - Yuancai Lv; Shiyu He; Shuting Liu; Zhendong Yu; Yanting Jiang; Yihui Hu; Yifan Liu; Chunxiang Lin; Xiaoxia Ye; Guifang Yang; Minghua Liu (Journal of Environmental Chemical Engineering, 2023)

Associations of urinary and blood cadmium concentrations with all-cause mortality in US adults with chronic kidney disease: a prospective cohort study - Jia Zhang; Xiao Wang; Zhibin Ma; Ying Dang; Yaya Yang; Shuting Cao; Changping Ouyang; Xiaoru Shi; Jinhua Pan; Xiaobin Hu (Environmental Science and Pollution Research, 2023)

A review of advanced oxidation process towards organic pollutants and its potential application in fracturing flowback fluid - Xing Li; Yang Bai; Xian Shi; Shuang Chang; Shuting Tian; Meiming He; Na Su; Pingya Luo; Wanfen Pu; Zhicheng Pan (Environmental Science and Pollution Research, 2023)

Free radical mechanism of toxic organic compound formations from o-chlorophenol - Xiaoyun Liu; Guorui Liu; Shuting Liu; Linjun Qin; Bingcheng Lin; Mingxuan Wang; Lili Yang; Minghui Zheng (Journal of Hazardous Materials, 2023)

Boreal winter stratospheric climatology in EC-EARTH: CMIP6 version - Froila M Palmeiro; Javier García-Serrano; Mario Rodrigo; Marta Abalos; Bo Christiansen; Shuting Yang (Climate Dynamics, 2023)
The performance of the European Consortium Earth-system model (EC-EARTH) in the boreal winter stratosphere is comprehensively assessed for the first time, in particular its version 3.3 that contributes to CMIP6. A 100-year long simulation with prescribed climatological boundary conditions and fixed radiative forcing, representative of present-day climate, is used to evaluate the simulation of the climatological stratospheric circulation and to identify model biases. Results show that EC-EARTH has a large issue with the vertical distribution of stratospheric temperature from the tropics to mid-latitudes, seemingly linked to radiative processes of ozone, leading to a biased warm middle-upper stratosphere. Associated with this model bias, EC-EARTH simulates a stronger polar vortex at upper-stratospheric levels while the Brewer-Dobson circulation at middle/lower levels is weaker than reanalysis. The amplitude of the climatological planetary waves is overall underestimated, but the magnitude of the background wave injection from the troposphere into the stratosphere is overestimated, related to a weaker polar vortex at lower-stratospheric levels and, thus, a less effective wave filtering. This bias in the westerly flow could have a contribution from parameterized waves. The overestimation of background wave driving is maximum in early-winter, and may explain the overestimated frequency of sudden stratospheric warmings at this time, as compared to reanalysis. The spatial distribution of wave injection climatology has revealed a distinctive role of the climatological planetary waves: while large-scale waves (wavenumbers 1–2) dominate the eddy heat flux over the North Pacific, small-scale waves (wavenumbers 3–4) are responsible for the doubled-lobe structure of the eddy heat flux over Eurasia. EC-EARTH properly simulates this climatological feature, although overestimates its amplitude over central Eurasia.

Poly- and Perfluoroalkyl Substances (PFAS) in Landfills: Occurrence, Transformation and Treatment - Man Zhang; Xianda Zhao; Dongye Zhao; Te-Yang Soong; Shuting Tian (Waste Management, 2023)

Non-equilibrium solute transport in dipole flow tracer test (DFTT) considering the mixing effect in the wellbore - Shuting Yang; Qi Zhu; Zhang Wen; Hamza Jakada (Journal of Hydrology, 2023)

Study on the interaction mechanism between Crocus sativus and Fusarium oxysporum based on dual RNA-seq - Juan Luo; Aolai Zhang; Kaifeng Tan; Shuting Yang; Xiaona Ma; Xiaolin Bai; Yutong Hou; Jie Bai (Plant Cell Reports, 2023)

Exposures to volatile organic compounds, serum vitamin D, and kidney function: association and interaction assessment in the US adult population - Wei Liu; Shuting Cao; Jixuan Ma; Da Shi; Linling Yu; Zi Ye; Meng Yang; Bin Wang; Weihong Chen (Environmental Science and Pollution Research, 2023)

Selenium (Se), Mercury (Hg) and Physicochemical Properties Co-Mediate the Bacterial Communities in a Typical Collapsed Lake Receiving Se- and Hg-containing Mine Water - Ruyi Yang; Linfeng Luo; Meng Zhu; Shuting Zan; Fuyu Guo; Yuhuan He; Xiaojing Shi; Bing Zhao (Water, Air, & Soil Pollution, 2022)

Simulated warming and low O2 promote N2O and N2 emissions in subtropical montane forest soil - Xiong Yang; Yingmo Zhu; Yunjian Xu; Xiangnan Li; Shuting Zhang; Qindong Qian; Lingling Wang; Jianping Wu; Zhe Chen (Journal of Soils and Sediments, 2022)

Assessing the influence of sea surface temperature and arctic sea ice cover on the uncertainty in the boreal winter future climate projections - Ho-Nam Cheung; Noel Keenlyside; Torben Koenigk; Shuting Yang; Tian Tian; Zhiqing Xu; Yongqi Gao; Fumiaki Ogawa; Nour-Eddine Omrani; Shaobo Qiao; Wen Zhou (Climate Dynamics, 2022)
We investigate the uncertainty (i.e., inter-model spread) in future projections of the boreal winter climate, based on the forced response of ten models from the CMIP5 following the RCP8.5 scenario. The uncertainty in the forced response of sea level pressure (SLP) is large in the North Pacific, the North Atlantic, and the Arctic. A major part of these uncertainties (31%) is marked by a pattern with a center in the northeastern Pacific and a dipole over the northeastern Atlantic that we label as the Pacific–Atlantic SLP uncertainty pattern (PA ∆SLP ). The PA ∆SLP is associated with distinct global sea surface temperature (SST) and Arctic sea ice cover (SIC) perturbation patterns. To better understand the nature of the PA ∆SLP , these SST and SIC perturbation patterns are prescribed in experiments with two atmospheric models (AGCMs): CAM4 and IFS. The AGCM responses suggest that the SST uncertainty contributes to the North Pacific SLP uncertainty in CMIP5 models, through tropical–midlatitude interactions and a forced Rossby wavetrain. The North Atlantic SLP uncertainty in CMIP5 models is better explained by the combined effect of SST and SIC uncertainties, partly related to a Rossby wavetrain from the Pacific and air-sea interaction over the North Atlantic. Major discrepancies between the CMIP5 and AGCM forced responses over northern high-latitudes and continental regions are indicative of uncertainties arising from the AGCMs. We analyze the possible dynamic mechanisms of these responses, and discuss the limitations of this work.

Influence of retreating Barents–Kara sea ice on the periodicity of El Niño–Southern Oscillation - Eun‐Sook Heo; Soon‐Il An; Ida Margrethe Ringgaard; Shuting Yang; Jens Hesselbjerg Christensen; Mi‐Kyung Sung (International Journal of Climatology, 2022)
The abrupt decline in sea ice in the Barents–Kara (BK) Sea because of global warming has been argued to influence not only higher latitudes but also the tropics. Using EC‐Earth model simulations, we demonstrated that the El Niño–Southern Oscillation (ENSO) period becomes longer when BK sea ice substantially decreases. As BK sea ice was forcibly reduced through nudging experiments, the mean Walker circulation shifted to the west, and the zonal sea surface temperature contrast in the tropical Pacific was enhanced. Consequently, the western Pacific mean thermocline became deeper, which reduced the sensitivity of oceanic wave response to wind forcing. Therefore, the oceanic Kelvin waves reflected by ENSO‐induced surface winds, a primary delayed negative feedback factor, were significantly weakened. Thus, ENSO phases could be sustained for longer.

Identification of nafamostat mesylate as a selective stimulator of NK cell IFN-γ production via metabolism-related compound library screening - Qinglan Yang; Shuju Zhang; Shuting Wu; Baige Yao; Lili Wang; Yana Li; Hongyan Peng; Minghui Huang; Qinghua Bi; Peiwen Xiong; Liping Li; Yafei Deng; et al. (Immunologic Research, 2022)
Natural killer (NK) cells play important roles in controlling virus-infected and malignant cells. The identification of new molecules that can activate NK cells may effectively improve the antiviral and antitumour activities of these cells. In this study, by using a commercially available metabolism-related compound library, we initially screened the capacity of compounds to activate NK cells by determining the ratio of interferon-gamma (IFN-γ) + NK cells by flow cytometry after the incubation of peripheral blood mononuclear cells (PBMCs) with IL-12 or IL-15 for 18 h. Our data showed that eight compounds (nafamostat mesylate (NM), loganin, fluvastatin sodium, atorvastatin calcium, lovastatin, simvastatin, rosuvastatin calcium, and pitavastatin calcium) and three compounds (NM, elesclomol, and simvastatin) increased the proportions of NK cells and CD3 + T cells that expressed IFN-γ among PBMCs cultured with IL-12 and IL-15, respectively. When incubated with enriched NK cells (purity ≥ 80.0%), only NM enhanced NK cell IFN-γ production in the presence of IL-12 or IL-15. When incubated with purified NK cells (purity ≥ 99.0%), NM promoted NK cell IFN-γ secretion in the presence or absence of IL-18. However, NM showed no effect on NK cell cytotoxicity. Collectively, our study identifies NM as a selective stimulator of IFN-γ production by NK cells, providing a new strategy for the prevention and treatment of infection or cancer in select populations.

Characterization, expression, and function analysis of AKR1A1 gene from yellow catfish (Tachysurus fulvidraco) - Long Yang; Shuting Zheng; Dan Kong; Shenghan Xiang; Jianfen Wu; Neng Wan; Wenxiu Sun; Wei Li (Fish Physiology and Biochemistry, 2022)

Whole-genome methylation analysis reveals epigenetic differences in the occurrence and recovery of hyperhydricity in Dendrobium officinale plantlets - Huiju Zhang; Min Shi; Shuting Su; Sikai Zheng; Miao Wang; Jun Lv; Xudong Wang; Quan Yang; Hongyang Gao (In Vitro Cellular & Developmental Biology - Plant, 2022)

Detection of pulmonary tuberculosis in children using the Xpert MTB/RIF Ultra assay on sputum: a multicenter study - Xiaoshan Peng; Qiong Liao; Min Fang; Yu Zhu; Yan Shi; Shuting Quan; Yacui Wang; Li Duan; Xiaomei Shi; Yang Liu; Manzhi Wang; Qingsong Wei; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2022)

The effects of manual airing strategies and architectural factors on the indoor air quality in college classrooms: a case study - Yanzhe Yu; Bei Wang; Shijun You; Tianzhen Ye; Wandong Zheng; Shen Wei; Shuting Yang; Yuanyuan Wang; Kun Li (Air Quality, Atmosphere & Health, 2022)

Spatiotemporal characteristics of human activity on coastal landscape of Laizhou Bay - Fan Yang; Jie Li; Jiaqing Wang; Jiantao Huang; Tong Qi; Yiman Liu; Tianyu Fu; Shuting Yu; Lingyan Zhao (Wetlands Ecology and Management, 2021)

Correction to: Temporal and spatial evolution patterns of drought in China over the past 500 years - Cuixia Wei; Bing Guo; Wenqian Zang; Fei Yang; Yuefeng Lu; Dafu Zhang; Hongwei Wu; Xiaoyan Zhen; Haorun Xue; Chao Meng; Shuting Chen; Xiao Yang; et al. (Arabian Journal of Geosciences, 2021)

Increased uterine androgen receptor protein abundance results in implantation and mitochondrial defects in pregnant rats with hyperandrogenism and insulin resistance - Yuehui Zhang; Min Hu; Fan Yang; Yizhuo Zhang; Shuting Ma; Dongqi Zhang; Xu Wang; Amanda Nancy Sferruzzi-Perri; Xiaoke Wu; Mats Brännström; Linus R. Shao; Håkan Billig (Journal of Molecular Medicine, 2021)
In this study, we show that during normal rat pregnancy, there is a gestational stage-dependent decrease in androgen receptor (AR) abundance in the gravid uterus and that this is correlated with the differential expression of endometrial receptivity and decidualization genes during early and mid-gestation. In contrast, exposure to 5α-dihydrotestosterone (DHT) and insulin (INS) or DHT alone significantly increased AR protein levels in the uterus in association with the aberrant expression of endometrial receptivity and decidualization genes, as well as disrupted implantation. Next, we assessed the functional relevance of the androgen-AR axis in the uterus for reproductive outcomes by treating normal pregnant rats and pregnant rats exposed to DHT and INS with the anti-androgen flutamide. We found that AR blockage using flutamide largely attenuated the DHT and INS-induced maternal endocrine, metabolic, and fertility impairments in pregnant rats in association with suppressed induction of uterine AR protein abundance and androgen-regulated response protein and normalized expression of several endometrial receptivity and decidualization genes. Further, blockade of AR normalized the expression of the mitochondrial biogenesis marker Nrf1 and the mitochondrial functional proteins Complexes I and II, VDAC, and PHB1. However, flutamide treatment did not rescue the compromised mitochondrial structure resulting from co-exposure to DHT and INS. These results demonstrate that functional AR protein is an important factor for gravid uterine function. Impairments in the uterine androgen-AR axis are accompanied by decreased endometrial receptivity, decidualization, and mitochondrial dysfunction, which might contribute to abnormal implantation in pregnant PCOS patients with compromised pregnancy outcomes and subfertility. Key messages The proper regulation of uterine androgen receptor (AR) contributes to a normal pregnancy process, whereas the aberrant regulation of uterine AR might be linked to polycystic ovary syndrome (PCOS)-induced pregnancy-related complications. In the current study, we found that during normal rat pregnancy there is a stage-dependent decrease in AR abundance in the gravid uterus and that this is correlated with the differential expression of the endometrial receptivity and decidualization genes Spp1 , Prl , Igfbp1 , and Hbegf . Pregnant rats exposed to 5α-dihydrotestosterone (DHT) and insulin (INS) or to DHT alone show elevated uterine AR protein abundance and implantation failure related to the aberrant expression of genes involved in endometrial receptivity and decidualization in early to mid-gestation. Treatment with the anti-androgen flutamide, starting from pre-implantation, effectively prevents DHT + INS-induced defects in endometrial receptivity and decidualization gene expression, restores uterine mitochondrial homeostasis, and increases the pregnancy rate and the numbers of viable fetuses. This study adds to our understanding of the mechanisms underlying poor pregnancy outcomes in PCOS patients and the possible therapeutic use of anti-androgens, including flutamide, after spontaneous conception.

Temporal and spatial evolution patterns of drought in China over the past 500 years - Cuixia Wei; Bing Guo; Wenqian Zang; Fei Yang; Yuefeng Lu; Dafu Zhang; Hongwei Wu; Xiaoyan Zhen; Haorun Xue; Chao Meng; Shuting Chen; Xiao Yang; et al. (Arabian Journal of Geosciences, 2021)

Heme oxygenase 1 plays a crucial role in swamp eel response to oxidative stress induced by cadmium exposure or Aeromonas hydrophila infection - Yuwei Zang; Shuting Zheng; Fang Tang; Long Yang; Xiping Wei; Dan Kong; Wenxiu Sun; Wei Li (Fish Physiology and Biochemistry, 2020)

Determining the contributions of climate change and human activities to the vegetation NPP dynamics in the Qinghai-Tibet Plateau, China, from 2000 to 2015 - Bing Guo; Baomin Han; Fei Yang; Shuting Chen; Yue Liu; Wenna Yang (Environmental Monitoring and Assessment, 2020)

Combined application of organic and inorganic fertilizers mitigates ammonia and nitrous oxide emissions in a maize field - Qinglong Yang; Peng Liu; Shuting Dong; Jiwang Zhang; Bin Zhao (Nutrient Cycling in Agroecosystems, 2020)

The combined application of organic and inorganic fertilizers increases soil organic matter and improves soil microenvironment in wheat-maize field - Qinglong Yang; Fengxia Zheng; Xucun Jia; Peng Liu; Shuting Dong; Jiwang Zhang; Bin Zhao (Journal of Soils and Sediments, 2020)

Circadian gene Clock participates in mitochondrial apoptosis pathways by regulating mitochondrial membrane potential, mitochondria out membrane permeablization and apoptosis factors in AML12 hepatocytes - Shuhong Yang; Yanyou Liu; Yimei Guo; Rong Liu; Fang Qi; Xiaoxue Li; Hang Yu; Shuting Cheng; Zhengrong Wang (Molecular and Cellular Biochemistry, 2020)

Barents-Kara sea ice and European winters in EC-Earth - Ida Margrethe Ringgaard; Shuting Yang; Eigil Kaas; Jens Hesselbjerg Christensen (Climate Dynamics, 2020)
The potential link between decreasing Barents-Kara sea ice and cold winters in Europe is investigated using the enhanced resolution (horizontal atmospheric resolution of $$\sim 80\,\hbox {km}$$ ∼ 80 km ) global, coupled climate model EC-Earth. Nudging sea ice only in the Barents-Kara Seas, five configurations of sea ice covers are used to assess the importance of the amount of sea ice in this region. Nudging in the coupled model is achieved by modifying the non-solar surface heat flux into the ice/ocean interface. The mean winter temperature response suggests a weak but statistically significant non-linear response with cooling over eastern Europe for moderate sea ice reductions in the Barents-Kara Seas, a weaker but still cold anomaly for minor reductions and warming for major reductions. However, this non-linear response is not reflected in the circulation. Instead, a negative mean sea level pressure anomaly over Barents-Kara Seas intensifies with sea ice reduction. In contrast to this, is the response in the coldest winters over central Europe: the larger the sea ice reduction, the stronger the Scandinavian pattern and the associated easterlies need to be to obtain cold winters over central Europe. The use of a coupled climate model is a potential explanation for the link between the intensified Scandinavian pattern and the cooling over Europe seen in this study, that is not observed in some atmosphere-only model studies.

Characteristics and mechanism of dolomitization in the ooids of the Cambrian Zhangxia Formation, Xiaweidian, China - Qiheng Guo; Zhenkui Jin; Xiaoer Zhu; Shuting Shi; Junjie Wang; Jinyi Wang; Yang Li; Shuo Li (Carbonates and Evaporites, 2020)

The influence of ENSO events on the stratospheric QBO in a multi-model ensemble - Federico Serva; Chiara Cagnazzo; Bo Christiansen; Shuting Yang (Climate Dynamics, 2020)
The Quasi-Biennial Oscillation (QBO) and the El Niño–Southern Oscillation (ENSO) are two dominant modes of climate variability at the Equator. There exist observational evidences of mutual interactions between these two phenomena, but this possibility has not been widely studied using climate model simulations. In this work we assess how current models represent the ENSO/QBO relationship, in terms of the response of the amplitude and descent rate of stratospheric wind regimes, by analyzing atmosphere-only and ocean–atmosphere coupled simulations from a large multi-model ensemble. The annual cycle of the QBO descent rate is well represented in both coupled and uncoupled models. Previous results regarding the phase alignment of the QBO after the 1997/98 strong warm ENSO event are confirmed in a larger ensemble of uncoupled experiments. However, in general we find that a relatively high horizontal resolution is necessary to reproduce the observed modulation of the QBO descent rate under strong ENSO events, while the amplitude response is generally weak at any horizontal resolution. We argue that biases in the mean state and over-dependence on parameterized wave forcing undermine the realism of the simulated coupling between the ocean and the stratosphere in the tropics in current climate models. The modulation of the QBO by the ENSO in a high emission scenario consistently differs from that in the historical period, suggesting that this relationship is sensitive to changes in the large-scale circulation.

Efficient Removal of Lead from Water Using Stabilized Iron Sulfide Nanoparticles: Effectiveness and Effects of Stabilizer - Yang Zhao; Shuting Tian; Yanyan Gong; Dongye Zhao (Water, Air, & Soil Pollution, 2019)

Effects of fertilizer type and rate on summer maize grain yield and ammonia volatilization loss in northern China - Qinglong Yang; Peng Liu; Shuting Dong; Jiwang Zhang; Bin Zhao (Journal of Soils and Sediments, 2019)

Production of eicosapentaenoic acid (EPA, 20:5n-3) in maize (Zea mays L.) through the alternative ∆8 desaturation pathway mediated by particle bombardment - Chenchen Wang; Xiao Yang; Haizhen Ma; Jiang Liu; Jing Chen; Jiedao Zhang; Shuting Dong; Baoxiu Qi; Xinzheng Li (Acta Physiologiae Plantarum, 2017)

Copper tolerant Elsholtzia splendens facilitates Commelina communis on a copper mine spoil - Ruyi Yang; Fuyu Guo; Shuting Zan; Gang Zhou; Wibke Wille; Jianjun Tang; Xin Chen; Jacob Weiner (Plant and Soil, 2015)

Tropical cyclones in enhanced resolution CMIP5 experiments - Nicholas Mossor Rathmann; Shuting Yang; Eigil Kaas (Climate Dynamics, 2014)

Comparative morphology of leaf epidermis in the genus Lithocarpus and its implication in leaf epidermal feature evolution in Fagaceae - Min Deng; Qiansheng Li; Shuting Yang; YanChun Liu; Jin Xu (Plant Systematics and Evolution, 2013)

A look at the ocean in the EC-Earth climate model - Andreas Sterl; Richard Bintanja; Laurent Brodeau; Emily Gleeson; Torben Koenigk; Torben Schmith; Tido Semmler; Camiel Severijns; Klaus Wyser; Shuting Yang (Climate Dynamics, 2012)

Effects of Developmental Exposure to TiO2 Nanoparticles on Synaptic Plasticity in Hippocampal Dentate Gyrus Area: an In Vivo Study in Anesthetized Rats - Xiaoyan Gao; Shuting Yin; Mingliang Tang; Jutao Chen; Zhongfei Yang; Wencai Zhang; Liang Chen; Bo Yang; Zhifeng Li; Yingying Zha; Diyun Ruan; Ming Wang (Biological Trace Element Research, 2011)